Evaluasi Pelaksanaan Pemilihan Umum Legislatif Tahun 2014 di Kabupaten Poso - Abdul Malik Saleh (Jurnal Ilmiah Administratie, 2016)
This study aims to determine the evaluation of the implementation of the legislative elections in Poso 2014. Technique of collecting data, by interview, documentation, and triangulation. Infomation retrieval techniques using purposive. The data analysis used the model Miles and Huberman. That are data reduction, data presentation and conclusion. The theory that used is the theory Bardach consist of four dimension, they are: technical feasibility, economy and financial possibility, political viability, and administration operability. Based on research result, that evaluating of the implementation of legislative elections in Poso 2014 is not effective, because from the four dimension according to Bardach, only two dimension that already met while the other two dimension have not been met. First, dimension of technical feasibility is already done accordance with applicable laws although in some ceses still need improvement in the implementation of better legislative elections. Second, dimention of economy and financial possibility, that the operation cost are used in the implementation of the legislative election need to get the attention to provide additional cost operational so that the role of organizer can be implemented optimaly. Third, political viability dimention, that all stages in the implementation of the election has been reachead and implemented according to predetermined schedule. Forth, administration operability dimention, that the impact problem on the implementation of legislative elections is less infrastructure and facilities in implementing the mission that are responsibility of the organizer.